2020
DOI: 10.1097/shk.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone, Ascorbic Acid, and Thiamine (HAT) Therapy Decreases Oxidative Stress, Improves Cardiovascular Function, and Improves Survival in Murine Sepsis

Abstract: Introduction: A small clinical trial showed HAT therapy improved survival but no studies have been reported in animal models to examine potential mechanisms. Methods: Sepsis was induced in female mice using the cecal ligation and puncture (CLP) model. Physiologic parameters including heart rate (HR), pulse distension (PD), and respiratory rate (RR) were measured noninvasively at baseline, 6 and 24 h post CLP. These measurements stratified mice into pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Elevated protein carbonyls have been observed previously in critically ill patients with sepsis [22]. The patients with the highest protein carbonyl values in our study had hypovitaminosis C. Interestingly, a pre-clinical animal model indicated that administration of high-dose vitamin C to mice with sepsis decreased protein carbonyl levels in the most severely ill [23]. This has not yet been demonstrated in human studies, however, based on vitamin C's potent antioxidant properties, it is possible that vitamin C administration to patients with pneumonia could decrease markers of oxidative stress.…”
Section: Discussionsupporting
confidence: 67%
“…Elevated protein carbonyls have been observed previously in critically ill patients with sepsis [22]. The patients with the highest protein carbonyl values in our study had hypovitaminosis C. Interestingly, a pre-clinical animal model indicated that administration of high-dose vitamin C to mice with sepsis decreased protein carbonyl levels in the most severely ill [23]. This has not yet been demonstrated in human studies, however, based on vitamin C's potent antioxidant properties, it is possible that vitamin C administration to patients with pneumonia could decrease markers of oxidative stress.…”
Section: Discussionsupporting
confidence: 67%
“…In one clinical trial, thiamine showed a statistically significance difference at lowering the lactate level compared to the control group and, therefore, possible reduc-tion in overall mortality [41,42,47,56]. The combination of thiamine, ascorbic acid, and corticosteroids has been suggested as a potential adjunctive therapy targeted at the non-oxygen delivery-dependent mechanisms of organ dysfunction in sepsis [41,42,47,[56][57][58]. Theoretically, based on these substances' mechanisms of action, their combination may have a synergistic effect in treating patients with septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with the highest protein carbonyl values measured in our study had hypovitaminosis C. Elevated oxidative stress could be both a cause and a consequence of the low vitamin C status observed in the patients. Interestingly, a pre-clinical animal model indicated that administration of high-dose vitamin C to mice with sepsis decreased protein carbonyl levels in the most severely ill [ 24 ]. This has not yet been demonstrated in human studies; however, based on the potent antioxidant properties of vitamin C, it is possible that vitamin C administration to patients with pneumonia could decrease markers of excessive oxidative stress.…”
Section: Discussionmentioning
confidence: 99%